Early and Late Complications After Liver Transplantation for Propionic Acidemia in Children: A Two Centers Study. Issue 3 (12th February 2015) - Charbit‐Henrion, F.; Lacaille, F.; McKiernan, P.; Girard, M.; de Lonlay, P.; Valayannopoulos, V.; Ottolenghi, C.; Chakrapani, A.; Preece, M.; Sharif, K.; Chardot, C.; Hubert, P.; et al.
<x xml:space="preserve">Abstract</x> Propionic acidemia (PA) is a severe metabolic disorder with cardiac and neurologic complications and a poor quality of life. Liver transplantation (LT) was thus proposed in PA to increase enzyme activity. We studied retrospectively LT in PA in two European centers. Twelve patients underwent 17 LTs between 1991 and 2013. They developed severe, unusual and unexpected complications, with high mortality (58%). When present, the cardiomyopathy resolved and no acute metabolic decompensation occurred allowing dietary relaxation. Renal failure was present in half of the patients before LT and worsened in all of them. We suggest that cardiac and renal functions should be assessed before LT and monitored closely afterward. A renal sparing immunosuppression should be used. We speculate that some complications may be related to accumulated toxicity of the disease and that earlier LT could prevent some of these consequences. As kidney transplantation has been performed successfully in methylmalonic acidemia, a metabolic disease in the same biochemical pathway, the choice of the organ to transplant could be further discussed.